Toolbox for monitoring, reporting, and verification (MRV) of greenhouse gass calculation in rice production - CGIAR Research Program on Rice (2020)
The toolbox is provided in form of an accessible and interactive platform which enables users to access the suitable tools/templates/guidelines according to their purposes. Part of the tools and guidelines are developed for use of the private sector while others mainly support governments in decision making and planning.